A novel LC-MS/MS assay for methylprednisolone in human plasma and its pharmacokinetic application - Sridhar Siddiraju; Mercy Lazar Lal Prasanth; Tadiboyina Sirisha (Elsevier, 2016)
Methylprednisolone is a synthetic glucocorticoid. In our report, the authors proposed a sensitive and selective liquid chromatography/tandem mass spectrometry (LC-MS/MS) assay for the determination of methylprednisolone applying budesonide as internal standard. Liquid-liquid extraction (LLE) having tert-butyl methyl ether (TBME) have been employed to extract methylprednisolone from the plasma samples. Immediately after reconstitution, the samples were chromatographed on a C18 column using an isocratic mobile phase composed of 10 mM ammonium formate buffer and acetonitrile (35:65, v/v). A flow rate of 1.00 ml/min was used to elute the analyte form the column. Analysis was carried out with an API-4000 LC-MS/MS instrument operated in multiple reaction-monitoring (MRM) mode. The linearity has been proven within the concentration range of 10.1-804 ng/ml in plasma samples. The precision (%CV) and accuracy results in five validation batches across five concentration levels were well within the acceptance limits. The drug was stable under different conditions. The particular assay has been proficiently put on pharmacokinetic study in healthy male subjects.